Conclusion: a hegemonic transition? - Böller, Florian; Werner, Welf (Hegemonic transition)
The concluding chapter summarizes the results presented in detail in the individual chapters and discusses implications for the future of the Liberal International Order. While there is sufficient evidence to suggest that the current hegemonic order is being challenged and that a hegemonic transition is taking place, these processes have, so far, not resulted in a new equilibrium. In other words, the hegemonic transition is far from being concluded. This dynamic constellation has created windows of opportunity, as well as new constraints, for states to redefine their position within the order. Therefore, it is highly unlikely that the situation of a hegemonic transition will simply disappear with the election of a new US president. On the one hand, domestic structural reasons suggest that the Biden administration will be limited in its capacity to remake US foreign policy after the Trump era. On the other hand, the widely diagnosed “rise of the rest” is projected to continue and the relative advantage of Western states will consequently diminish further. The COVID-19 pandemic has the potential to act as a catalyst in this regard. Overall, this suggests that the current hegemonic vacancy may continue to destabilize the global order in the medium and long term.